Does Globalization Make the World More Equitable? - Kurt Bayer (Intervention. European Journal of Economics and Economic Policies, 2008)
First paragraph: Globalization is not a new phenomenon. A first phase occurred during the colonization of Africa, Asia and Latin America when raw materials for Europe were extracted, slave labor shipped across the world and markets developed as outlets for European commodities. This critical phase can be dated from the 1850s to World War I. During that time the share of exports in world GDP doubled to eight percent, 60 million Europeans emigrated to America, similar numbers from China and India to other South Asian and African countries. Migration flows reached ten percent of world population, trade relations flourished. This trend reversed after World War I: by the 1950s, the share of exports in world GDP had fallen back to its 1870 level of four percent, per capita growth was lower by one third, partly as a result of the wars, partly as a result of the breakdown of trade and investment relations due to protectionist policies and a dramatic fall in world demand in the course of the Great Depression.
Keywords: 330